Epidermal Barrier Dysfunction in Atopic Dermatitis - Tiago Fernandes Gomes; Rebeca Calado; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Impaired skin barrier is one of the hallmarks of atopic dermatitis (AD), with abnormalities in the cornified envelope, lipid lamellae, tight junctions and cutaneous microbiome. These findings are also present in nonlesional skin of AD individuals, suggesting that epidermal barrier defects may be the initial step towards the development of AD and eventually other atopic diseases (atopic march). It is currently known that pathophysiology of AD involves an interplay between this dysfunctional skin barrier and a predominantly type 2 skewed innate and adaptive immune responses, which further disrupt the skin barrier through type 2 cytokines. In this setting, there is enhanced penetration of environmental and food allergens through a deficient barrier, leading to an increased susceptibility to sensitization. During the sensitization process, thymic stromal lymphopoietin (TSLP) polarizes skin dendritic cells to a T-helper 2 response, and TSLP seems to be a key cytokine in the sensitization of food allergy, allergic asthma and rhinitis. In this review, the authors describe the current knowledge of the pathophysiology of the epidermal barrier, its disruption in AD and how it may be involved in the development of atopic comorbidities and the role of barrier repair therapy on the prevention of the atopic march progression.